UTILIZING LEARNING MEDIA TO FOSTER STUDENTS’ LEARNING ACTIVITIES AT GRADE V SDN SEROJA - Hilya Aulia; Nana Hendracipta Hendracipta; Sastra Juanda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the use of instructional media to increase students’ learning activities at grade V SDN Seroja. This research used qualitative methods using three data collection techniques, namely observation, interviews, and documentation. The results of this study indicated that the teacher was able to utilize learning media in the learning activity. It was observed that in the process of utilizing instructional media, the teacher first compiled the lesson plans, learning materials selections, the use of learning media, students’ responses and the process of assessing learning activities so that students were able to receive the results of the process of using learning media. Then, in learning activities, the students could understand the learning material better; the students had meaningful experiences; and their learning activities increased. Thus, this learning media increased the students’ learning activities.